Preparation and Physicochemical Properties of Corn Protein Hydrolysates with Anti-adhesive Activity against Helicobacter pylori - Quanxin WANG; Zhengfei MIAO; Xiang GAO; Guanlong LI; Xiaolan LIU (Shipin gongye ke-ji, 2025)
The population of Helicobacter pylori (H. pylori) infection in China is large. It is of great significance to find safe and effective new functional food ingredients for the treatment of H. pylori infection. In this study, CPN and CPNA two corn protein hydrolysates were prepared. The molecular weight distributions and amino acid compositions of the hydrolysates were further analyzed. The results showed that the optimal conditions prepared by Neutrase were substrate concentration 15% (protein-based), pH7.0, temperature 45 ℃, enzyme amount 400 U/g, and hydrolysis time 150 min. The H. pylori adhesion inhibition rate was 54.83%±0.56% at the protein concentration of 4 mg/mL in vitro. On this basis, The H. pylori adhesion inhibition rate of CPNA was significantly reduced by the Neutrase and Alcalase synergistic hydrolysis in vitro (P<0.05). Further physicochemical properties analyses of the hydrolysates were performed to explore the potential relationship between hydrolysate properties and anti-adhesive activity against H. pylori. Compared with CPNA, CPN was characterized by a smaller molecular weight distribution, a higher proportion of hydrophobic amino acids (increased by 4.76%), and greater surface hydrophobicity (increased by 28.03%). In addition, good antioxidant activity in vitro was also possessed by CPN. It was suggested that it could be used as a functional food base for the prevention of H. pylori infection. A new idea and theoretical basis for the high-value utilization of corn protein were provided by this study.